Study on Some Mechanical Properties of Waste PET and Sand Composites - Atiku, Jamila Umar; Atoshi, Ago Mikyitsabu; Alheri, Andrew; Aaron, Andema Kanadi; Dass, Peter Micheal (Darul Yasin Al Sys, 2025)
The escalating issue of plastic waste, particularly polyethylene terephthalate (PET), poses significant environmental challenges in Nigeria due to its resistance to natural degradation. This study aims to investigate the feasibility of recycling waste PET into composite materials by incorporating sand sourced from three distinct locations. Composites were formulated by blending PET waste with sand in varying ratios, designated as samples A, B, and C. We meticulously evaluated the mechanical properties of these composites, focusing on impact strength, compressive strength, tensile strength, and hardness. The findings reveal that increasing sand content correlates with a decrease in impact strength, a trend consistent across all samples as PET content diminishes. Although compressive strength initially exhibits a slight increase with additional sand, it ultimately enhances with greater PET proportions. Conversely, tensile strength experiences a modest rise with increased sand and a significant improvement with elevated PET levels. Notably, hardness decreases with rising sand content but improves with higher PET levels. These results highlight the potential of PET-sand composites as sustainable construction materials, representing a practical approach to mitigating plastic waste while contributing to eco-friendly building practices.